Case study of tenure-track early career faculty in a college of education - Esping, Gretchen Revay (Kansas State University, 2010)
This dissertation examines an understudied group according the American Council on Education: the tenure-track early career faculty (ECF). The focus is on the culturalization, socialization, academic culture, and emergent themes discerned from ten semi-structured interviews with tenure-track ECF. This qualitative bounded system case study was conducted in the context of a Midwestern Carnegie I Research Land-Grant Institution, an institution with emphasis on teaching, research, and service. Ten semi-structured interviews were conducted and transcribed. From these, codes, categories, patterns, and themes were found. Additional documentation was also considered such as participants’ resumes and the faculty handbook, COE: Orientation to COE A Guide for Faculty 2008-2009. The themes included a reliance on socialization from the parent degree granting institution, and an overall request for balance between professional and personal life. In addition the ECFs need mentoring at their new institution in research, writing and publication, in professional identity, and socialization to tacit knowledge via cognitive apprenticeship. A recommendation is that there be a bi-directional conversation on socialization, rather than a top down approach.
Keywords: Early Career Faculty (ECF); College of Education; Case study; Cognitive apprenticeship; Socialization; Academic culture; Education, Administration (0514); Education, Higher (0745); Education, Teacher Training (0530)